Erratum: Erst, A.S., Wang, W., Yu, S.X., Xiang, K.L., Wang, J., Shaulo, D.N., Smirnov, S.V., Kushunina, M., Sukhorukov, A.P. & Nobis, M. (2017) Two new species and four new records of Aquilegia (Ranunculaceae) from China. Phytotaxa 316 (2): 121–137. - Erst, Andrey S.; Wang, Wei; Yu, Sheng-Xiang; Xiang, Kunli; Wang, Jian; Shaulo, Dmitry N.; Smirnov, Sergey V.; Kushunina, Maria; Sukhorukov, Alexander P.; Nobis, Marcin (Phytotaxa, 2017)
N/A